Embrio Perkembangan Tafsir dalam Masyarakat Sunda (Vernakularisasi Kitab Marah Labid Syaikh Nawawi al-Bantani) - Kurniawan, Rifai (Al-Manar: Jurnal Kajian Alquran dan Hadis, 2023)
In the archipelago, interpretation development differs from in areas where Arabic is used daily, such as in Egypt and other parts of Central Timor. Therefore, they are starting to interpret using local languages used to communicate with each other, including Sundanese people. In this case, the author wants to reveal the embryo by tracing it historically; it turns out that at first, it was found that interpretations were in Sundanese or cultural languages that continued for several years. Then, it developed until a complete interpretation emerged whose knowledge was recognized worldwide, namely Sheikh Nawawi Al-Bantani. His work, Marah Labid, has a distinctive Indonesian style in discussing and interpreting the contents of the verses of the Koran. From the research results, it can be concluded that Marah Labid combines ijmali (global) and tahlili (analysis) interpretation methods simultaneously. This research method is descriptive-qualitative through analysis of library research. The research concludes that the Islamic religion entering Indonesia did not immediately emphasize understanding Sharia law. When society begins to participate in its religion, understanding the Qur'an comes in the form of interpretations. In the 19th century, there was a local cultural interpretation of the Sundanese language by Nawawi al-Bantani in its work, Marah Labid.